2019
DOI: 10.1111/vop.12627
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcome following phacoemulsification in English Cocker Spaniels with suspected progressive retinal atrophy: A retrospective multicenter study of 54 cases (2002‐2017)

Abstract: Objective To describe the visual outcome following phacoemulsification in English Cocker Spaniels (ECS) affected by cataracts and suspected progressive retinal atrophy (PRA). Animals studied Fifty‐four client‐owned dogs. Procedures A multicenter, retrospective study was performed including ECS with suspected PRA which underwent phacoemulsification. PRA was suspected on ophthalmic examination before and after surgery, and/or after electroretinography (ERG) was performed. Visual outcome was assessed by menace re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, ERG is severely reduced when only part of the retinal function remains due to retinal degeneration, but VEPs are detectable. In a study by Koll-Hampp et al, although ERG was undetectable, English Cocker Spaniels with suspected PRA showed signi cant visual improvement after phacoemulsi cation [34]. VEPs were not assessed in their study; however, there may have been an association between VEPs and visual improvement after phacoemulsi cation in patients with cataracts with undetectable ERG.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, ERG is severely reduced when only part of the retinal function remains due to retinal degeneration, but VEPs are detectable. In a study by Koll-Hampp et al, although ERG was undetectable, English Cocker Spaniels with suspected PRA showed signi cant visual improvement after phacoemulsi cation [34]. VEPs were not assessed in their study; however, there may have been an association between VEPs and visual improvement after phacoemulsi cation in patients with cataracts with undetectable ERG.…”
Section: Discussionmentioning
confidence: 86%
“…A high prevalence of goniodysgenesis was found in eyes from Cocker Spaniels that were removed due to glaucoma after surgery, but the prevalence of goniodysgenesis in eyes that did not develop glaucoma, and in eyes that developed glaucoma but were not enucleated, was not assessed. In a study of phacoemulsification in English Cocker spaniels with progressive retinal atrophy by Koll‐Hampp et al, 21 demonstrated that of 16 dogs with gonioscopic abnormalities prior to phacoemulsification, none developed glaucoma after surgery, however, follow‐up times for these 16 dogs were not reported. In a case‐control study, Lannek and Miller observed 70% of dogs in the postoperative glaucoma group had narrow or closed ICAs compared with 52% in the postoperative nonglaucoma group but the P ‐value for this association was high 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed whether preoperative abnormal gonioscopy findings are risk factors for postoperative glaucoma after phacoemulsification 8,21‐23 with varied results. The objective of this study was to assess whether gonioscopy status prior to cataract surgery is associated with development of postoperative glaucoma in dogs.…”
Section: Introductionmentioning
confidence: 99%